University Malaysia Perlis (UniMAP) as an agent in propagating occupational safety and health programmes among small business units in Perlis vis-a-vis Occupational Safety and Health Act 1994 - Evawaynie Valquis, Md. Isa; Azuddin, Bahari, Lt Kol (B) (National Institute of Occupational Safety and Health (NIOSH), 2008)
Organized by National Institute of Occupational Safety and Health (NIOSH), 20th - 22nd August 2007 at Genting International Convention Centre (GICC), Genting Highlands, Malaysia.